Acellular Pertussis Vaccines Induce CD8+ and CD4+ Regulatory T Cells That Suppress Protective Tissue-Resident Memory CD4+ T Cells, in Part via IL-10 - Mills, Kingston; Moran, Barry (My University, 2025)
Tissue-resident memory T (TRM) cells play a key role in sustained protective immunity against Bordetella pertussis infection of the nasal mucosa. Current alum-adjuvanted acellular pertussis (aP) vaccines protect against severe pertussis disease but fail to prevent nasal infection with B. pertussis. Here we demonstrate that immunization of mice with an aP vaccine failed to generate respiratory TRM cells, but did induce antigen-specific CD4+ Treg cells that expressed Foxp3, CD49b, PD-1 and LAG-3, and CD8+ Treg cells that expressed CD122, PD-1, and IL-10. B. pertussis-specific CD4+ and CD8+ T cell lines established from aP-immunized mice expressed the regulatory markers and suppressed activation of Th1 and Th17 cells. Blockade of IL-10 signaling during aP immunization or B. pertussis challenge promoted the induction of IL-17-secreting CD4+ TRM responses and enhanced bacterial clearance from the nose. Addition of the adjuvant LP-GMP, comprising TLR2 and STING agonists, to the aP vaccine and delivery by the nasal route promoted the induction of antigen-specific IL-17-producing CD4+ TRM cells and enhanced vaccine efficacy. Our findings demonstrate that aP vaccines suppress the induction of protective TRM cells in part through the induction of CD4+ and CD8+ Treg cells, which can be overcome using a potent adjuvant and delivery of the vaccine intranasally.
PUBLISHED
Cited by: 0